2021
DOI: 10.1101/2021.04.07.438881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid, but limited, zooplankton adaptation to simultaneous warming and acidification

Abstract: Predicting the response of marine metazoans to climate change is hampered by a lack of studies on evolutionary adaptation, particularly to combined warming and acidification. To test whether the ubiquitous marine copepod Acartia tonsa can adapt to warmer and acidified conditions, we tracked five fitness-relevant life-history traits for 25 generations (~ 1 year) with a 2 x 2 factorial design of temperature (18 C, 22 C) and pCO2 (400, 2000 μatm). Initially, combined warm, acidic conditions decreased egg producti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Across the stress temperatures evaluated, copepods adapted to OWA conditions exhibit a decrease in maximum survivorship in addition to a shift towards cooler temperatures. The reduced thermal tolerance for OWA copepods could also be explained by antagonistic interactions of warming and acidification, which we observed after 25 generations of adaptation [40]. Copepods from OWA lineages (OWA OWA and OWA AM ) and those that developed in OWA conditions (AM OWA ) show significantly lower high-temperature thermal performance relative to AM AM , with the OWA OWA treatment exhibiting the lowest LD 50 (figure 2a).…”
Section: Discussion (A) Costs Of Adaptationmentioning
confidence: 81%
See 2 more Smart Citations
“…Across the stress temperatures evaluated, copepods adapted to OWA conditions exhibit a decrease in maximum survivorship in addition to a shift towards cooler temperatures. The reduced thermal tolerance for OWA copepods could also be explained by antagonistic interactions of warming and acidification, which we observed after 25 generations of adaptation [40]. Copepods from OWA lineages (OWA OWA and OWA AM ) and those that developed in OWA conditions (AM OWA ) show significantly lower high-temperature thermal performance relative to AM AM , with the OWA OWA treatment exhibiting the lowest LD 50 (figure 2a).…”
Section: Discussion (A) Costs Of Adaptationmentioning
confidence: 81%
“…Acartia tonsa (Copepoda: Calanoida) is an estuarine and coastal foundational species [25,26], used in previous experimental evolution studies [28,33,40]. Acartia tonsa was collected June 2016 from Long Island Sound CT USA (41.3 N, −72.0 W).…”
Section: Materials and Methods (A) Study Organism And Culturingmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of these thermal performance curves found that instead of a strict thermodynamic constraint, slightly hotter adaptation is more favorable for phytoplankton (Kontopoulos et al, 2020). Despite the possibility of some plankton species adapting to thermal changes (O'Donnell et al, 2018;Dam et al, 2021), global warming poses a threat to the existing plankton biogeography with cascading effects on the higher trophic levels (Henson et al, 2021). Studies suggest a poleward shift of some species and reduced diversity in the tropics (Thomas et al, 2012;Benedetti et al, 2021;Freḿont et al, 2022).…”
mentioning
confidence: 99%
“…All data and code for analysing and visualizing the data are deposited into a Zenodo repository located at: [92]. Transcriptomic data are deposited in Genbank with BioProject Accession number PRJNA966098.…”
Section: Data Accessibilitymentioning
confidence: 99%